Inhibitor CARDS Toxin sebagai Pengobatan Pnemonia pada Biji Jintan Hitam (Nigella sativa): CARDS Toxin Inhibitor as Pnemonia Treatment in Black Cumin Seed (Nigella sativa) - Anwar, La Ode Muhammad; Pramestyani, Embriana Dinar; Adiwisastra, Nuzul Gyanata; Muslih, Hamdan Faisal; Romli, Cindy Junita; Jannah, Zam Zam Zainatul; Harahap, Kurnia Pebriyanti; Okhanza, Awanda Pramudita; Lestari, Sri (Jurnal Sains dan Kesehatan, 2025)
CARDS toxin is a protein component that triggers pnemonia. The purpose of this research is to find out what compounds can inhibit CARDS toxin in black cumin seed compounds. CARDS toxin was downloaded on the PDB site with the code 4TLW. The control used is hydroxychloroquine compound. The docking results showed inhibition of CARDS toxin, namely quercetin 3-(6''''-feruloylglucosyl)-(1->2)-galactosyl-(1->2)-glucoside (-16.4 kcal/mol), gramisterol (-10.0 kcal/mol), taraxerol (-9.6 kcal/mol) and quercetin (-9.0 kcal/mol) compared to the control. SwissADME pharmacokinetic values showed that the compounds were lipophilic, namely gramisterol and taraxerol. Absorption values showed that only quercetin 3-(6''''-feruloylglucosyl)-(1->2)-galactosyl-(1->2)-glucoside and quercetin compounds had high absorption values while other compounds were still very low. Only quercetin compound inhibited CYP1A2. Bioavailability values of all compounds were more than 10%. All plant compounds are possible to be synthesized (range score 1-10). Keywords:          CARDS Toxin, Pnemonia, Mycoplasma pneumoniae   Abstrak CARDS toxin merupakan kompenen protein pencetus penyakit pnemonia. Tujuan dari penelitian ini adalah untuk mengetahui senyawa apa saja yang mampu menghambat CARDS toxin pada senyawa biji jintan hitam. CARDS toxin diunduh pada situs PDB dengan kode 4TLW. Kontrol yang digunakan adalah senyawa hydroxychloroquine. Hasil docking menunjukan terdapat penghambatan CARDS toxin yaitu quercetin 3-(6''''-feruloylglucosyl)-(1->2)-galactosyl-(1->2)-glucoside (-16.4 kcal/mol), gramisterol (-10.0 kcal/mol), taraxerol (-9.6 kcal/mol) dan quercetin (-9.0 kcal/mol) dibanding dengan kontrol. Nilai farmakokinenik SwissADME menunjukan senyawa bersifat lipofilik yaitu gramisterol dan taraxerol. Nilai absorbsi menunjukan hanya senyawa quercetin 3-(6''''-feruloylglucosyl)-(1->2)-galactosyl-(1->2)-glucoside dan quercetin memiliki nilai absorbsi yang tinggi sedanggkan senyawa lain masih sangat rendah. Hanya senyawa quercetin yang menghambat CYP1A2. Nilai bioavabilitas semua senyawa lebih dari 10%. Semua senyawa tanaman memungkinkan untuk dapat disintesis (range score 1-10). Kata Kunci:         CARDS Toxin, Pnemonia, Mycoplasma pneumoniae